Broad Clinical Involvement in a Family Affected by the Fragile X Premutation - CHONCHAIYA, WEERASAK (2009)
The mutations in the FMR1 gene have been described as a family of disorders called fragile X-associated disorders (FXD) including fragile X syndrome (FXS), fragile X-associated tremor/ ataxia syndrome (FXTAS), primary ovarian insufficiency and other problems associated with the premutation, such as hypothyroidism, hypertension, neuropathy, anxiety, depression, attention deficit hyperactivity disorders and autism spectrum disorders. The premutation is relatively common in the general population affecting 1 of 130–250 female individuals and 1 of 250–800 male individuals. Therefore, to provide appropriate treatment and genetic counseling for all of the carriers and affected individuals in a family, a detailed family history that reviews many of the disorders that are related to both the premutation and the full mutation should be carried out as exemplified in these cases. To facilitate the integration of this knowledge into clinical practice, this is the first case report that demonstrates only premutation involvement across 3 generations.